Kompetensi Profesional Guru Anak Usia Dini di PAUD IT Al Hasanah Kota Bengkulu - Nila Suci Ramadhan; Evi Selva Nirwana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to evaluate the competencies of early childhood educators at PAUD IT Al Hasanah in Bengkulu City. The research method employed is qualitative descriptive, with the subjects being the educators at PAUD IT Al Hasanah in Bengkulu City. Data collection was conducted directly through observation, interviews, and documentation, with data analysis following the Miles and Huberman model, involving an ongoing data analysis process parallel to data collection in qualitative research. This means that data analysis occurs not only after all data is gathered but also from the beginning of the data collection process. The research findings indicate that educators at PAUD IT Al Hasanah in Bengkulu City possess strong professional capabilities that align with the needs and developmental stages of early childhood. Educators can effectively communicate material clearly and understandably to children, ensuring swift comprehension of each concept taught. Additionally, educators actively impart religious values through activities such as memorizing short verses and hadiths, tailored to the needs and characteristics of children in the PAUD IT Al Hasanah environment. However, the limited variety and appeal of instructional media have led to a lack of creativity in the learning process. Therefore, an enhancement in the diversity and attractiveness of instructional media is necessary to improve the effectiveness of educators in teaching and supporting the holistic development of children. Collaboration in enhancing educators' competencies and diversifying instructional media is anticipated to have a positive impact on the quality of early childhood education at PAUD IT Al Hasanah in Bengkulu City. Keywords: Professional Competence, Teacher